The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10897-017-0153-0
|View full text |Cite
|
Sign up to set email alerts
|

Working with the Hmong Population in a Genetics Setting: an Interpreter Perspective

Abstract: The aim of this pilot qualitative study was to describe the experiences and beliefs of medical interpreters when working with genetic counselors and other genetic providers caring for Hmong patients who are not native English speakers. Specific goals were to identify interpreters' thoughts and perceptions on (a) their roles during sessions, (b) unique challenges in a genetics session, (c) knowledge genetics providers need when working with Hmong patients and interpreters, and (d) supports and training needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Another related limitation is that we did not interview our interpreters to understand their views concerning their role. Other genetic counseling interpreter studies among Hmong individuals have shown that interpreters can view their roles differently, such as a verbatim translator or as a cultural broker (Krieger, Agather, Douglass, Reiser, & Petty, ). The self‐perceived role of the interpreter could impact communication in a genetic counseling session.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Another related limitation is that we did not interview our interpreters to understand their views concerning their role. Other genetic counseling interpreter studies among Hmong individuals have shown that interpreters can view their roles differently, such as a verbatim translator or as a cultural broker (Krieger, Agather, Douglass, Reiser, & Petty, ). The self‐perceived role of the interpreter could impact communication in a genetic counseling session.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Interpreters' survey responses indicated that most had no training in genetics, and that training on basic genetic concepts would enhance their ability to interpret effectively for genetic counseling. Similarly, a recent study on the perspectives of HIs serving Hmong patients in a genetics setting also identified the need for training in genetics and genetic concepts as a way to mitigate the difficulties associated with interpreting (Krieger et al, 2018).…”
Section: Trust In the Relationship Between Interpreters And Genetic Cmentioning
confidence: 99%
“…Despite their critical role in language discordant encounters and cross-cultural patient-provider communication, the voice of HIs is surprisingly absent from the literature (Hudelson, 2005). There is little research in genetic counseling concerning the role of HIs, and it largely addresses interpretation as part of a broader account of genetic services for culturally diverse, LEP patient populations (Hunt & De Voogd, 2007;Krieger, Agather, Douglass, Reiser, & Petty, 2018;Saleh, Barlow-Stewart, Meiser, & Muchamore, 2009). This exploratory study examined the perspectives of both GCs and HIs on CGC sessions conducted with remote (telephone or video) interpreters.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-structured interview questions for genetic counselors (Table 2) were developed using results from a previously unpublished pilot study done by Krieger, M. et al (2014) that interviewed Hmong medical interpreters about their experiences in medical genetics appointments. The questions were further developed and reviewed for appropriateness with help from a genetic counselor with greater than 30 years' experience, a medical geneticist, and two consultants from the Demographic questions were included in the interview.…”
Section: Instrumentationmentioning
confidence: 99%
“…They found that 70% of the study participants found the kit easy to understand, however the study only included Hmong individuals who could read and speak English. To try to quantify Hmong interpreter experiences in genetics appointments, an internal unpublished University of Wisconsin pilot study interviewed six Hmong interpreters regarding their experiences working with Hmong patients in genetic counseling sessions (Krieger et al 2014). The study found that most of the medical interpreters felt their training did not prepare them for genetics appointment.…”
mentioning
confidence: 99%